Auditing Standards, Professional Judgment, and Audit Quality - Gao, Pingyang; Zhang, Gaoqing (The Accounting Review, 2019)
ABSTRACT We propose a model to study how auditing standards affect audit quality. We posit that both auditors' incentives and expertise are relevant for audit effectiveness. Auditing standards are useful in mitigating the auditors' possible misalignment of interest with investors. However, auditing standards also restrict auditors' exercise of professional judgment, which, in turn, leads to compliance mentality and reduces auditors' incentives to become competent in the first place. We identify the conditions under which stricter auditing standards increase or decrease audit quality. Moreover, stricter auditing standards always increase audit fees, but can benefit auditors at firms' expense. The model also generates many testable empirical predictions.